Perceptions of career and technical education, two-year technical colleges, and four-year institutions that potentially influence students' post-secondary choices - Baus, Susan L. (University of Wisconsin--Stout, 2018)
Currently, there is limited matriculation of local high school graduates in the Sturgeon Bay area into technical or vocational colleges (Sturgeon Bay School District Post-Secondary Plans, n.d.) despite the growing need for skilled workers. There is also no research as to what factors may contribute to this limited matriculation. The purpose of this research project is to gain an understanding of the perceptions of Sturgeon Bay High School sophomore and junior students' parents/guardians and Door County Counselors regarding CTE, two-year technical college, and four-year institutions. A survey was created for both Sturgeon Bay High School sophomore and junior students' parents/guardians and Door County Counselors to determine those perceptions. While survey results from both Sturgeon Bay High School parents/guardians and Door County counselors showed that their perceptions of CTE, two-year technical colleges, and four-year institutions were mixed; the results found that overwhelmingly parents/guardians are most concerned with the rising costs of a post-secondary education and want their children to get an education for a job that will provide them a life-sustaining wage without going into significant debt to attain it.
Keywords: Sturgeon Bay (Wis.); High school students; Vocational education